ENCEPHALITIS ANTI N-METHYL-D-ASPARTATE RECEPTORS - Suryani, Shila; Wisudarti, Calcarina Retno Fitriani (Mandala Of Health, 2023)
Background : Anti-N-Methyl-D-Aspartate receptor encephalitis is an autoimmune disease where the incidence is still rare which is characterized by complex neuropsychiatric syndrome. In severe stages, it can cause morbidity and mortality so it requires adequate intensive therapeutic management. Cases: 1) Male, 23 years old diagnosed with NMDAR encephalitis at an advanced stage in 10 days of treatment. Patient was given plasma exchange therapy three times and steroids did not respond then given rituximab, did not respond as expected. 2) A 19-year-old male diagnosed with NMDAR encephalitis at an advanced stage on the 7th day of hospitalization. Patient was given plasma exchange therapy 7 times and steroids. The patient showed an improved response to the third plasma exchange therapy, the patient could weaned from the ventilator and then transferred from the ICU. Conclusion: NMDAR encephalitis at an advanced stage requires long intensive care. Immunotherapy is the first-line therapy for NMDAR encephalitis. Immunotherapy options in severe cases can be given plasma exchange in combination with steroids. Rapid diagnosis and early initiation of therapy can provide better outcomes, reduce complications of nosocomial infections and reduce length of stay in the ICU.